ANTROPOLOGI GENDER DALAM PEMBAGIAN KERJA SECARA SEKSUAL MASYARAKAT NELAYAN - Nur Iza Dora (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2017)
This study was conducted on fisherman community at Percut Village, Percut Sei Tuan, Deli Serdang Regency, North Sumatera Province. Focus of this study  was to describe woman involvement on public sector  by working as fisherwoman and what their strategies are in building household economy. Aim of the research is to describe  fisherwoman’s life at Percut Village. Approach used was qualitative approach with data collecting through participated observation and in-dept interview.